Parametric Estimation of Reference Signal Intensity for Semi-Quantification of Tau Deposition: A Flortaucipir and [18F]-APN-1607 Study - Zhang, Huiwei; Wang, Min; Lu, Jiaying; Bao, Weiqi; Li, Ling; Jiang, Jiehui; Zuo, Chuantao; , and Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Neuroscience, 2021)
Background: Tau positron emission tomography (PET) imaging can reveal the pathophysiology and neurodegeneration that occurs in Alzheimer’s disease (AD) in vivo. The standardized uptake value ratio (SUVR) is widely used for semi-quantification of tau deposition but is susceptible to disturbance from the reference region and the partial volume effect (PVE). To overcome this problem, we applied the Parametric Estimation of Reference Signal Intensity (PERSI) method—which was previously evaluated for flortaucipir imaging—to 2 tau tracers, flortaucipir and [18F]-APN-1607. Methods: Two cohorts underwent tau PET scanning. Flortaucipir PET imaging data for cohort I (65 healthy controls [HCs], 60 patients with mild cognitive impairment [MCI], and 12 AD patients) were from the Alzheimer’s Disease Neuroimaging Initiative database. [18F]-APN-1607 ([18F]-PM-PBB3) PET imaging data were for Cohort II, which included 21 patients with a clinical diagnosis of amyloid PET-positive AD and 15 HCs recruited at Huashan Hospital. We used white matter (WM) postprocessed by PERSI (PERSI-WM) as the reference region and compared this with the traditional semi-quantification method that uses the whole cerebellum as the reference. SUVRs were calculated for 7 regions of interest including the frontal, parietal, temporal, and occipital lobes; anterior and posterior cingulate; precuneus; and Braak I/II (entorhinal cortex and hippocampus). Receiver operating characteristic (ROC) curve analysis and effect sizes were used to compare the 2 methods in terms of ability to discriminate between different clinical groups. Results: In both cohorts, regional SUVR determined using the PERSI-WM method was superior to using the cerebellum as reference region for measuring tau retention in AD patients (eg, SUVR of the temporal lobe: flortaucipir, 1.08±0.17 and [18F]-APN-1607, 1.57±0.34); and estimates of the effect size and areas under the ROC curve (AUC) indicated that it also increased between-group differences (eg, AUC of the temporal lobe for HC vs AD: flortaucipir, 0.893 and [18F]-APN-1607: 0.949). Conclusions: The PERSI-WM method significantly improves diagnostic discrimination compared to conventional approach of using the cerebellum as a reference region and can mitigate the PVE; it can thus enhance the efficacy of semi-quantification of multiple tau tracers in PET scanning, making it suitable for large-scale clinical application.